Models of engagement between the state and the faith sector in sub-Saharan Africa – a systematic review. Issue 5 (4th July 2017) - Whyle, Eleanor; Olivier, Jill
ABSTRACT: In sub-Saharan Africa many individuals rely on non-state health providers, and engagement between state and non-state providers is increasingly common. Little analytic work has been done on the varied models of engagement, resulting in a lack of clarity about the promises and challenges of public–private engagement (PPE) for health. Despite their prevalence, PPEs often fail. Faith-based health providers (FBHPs) form a significant proportion of the non-state health sector in sub-Saharan Africa, and the number of partnerships with FBHPs is increasing. Building on a prior systematic review project that developed a typology of organisational models for PPE for health, this article reports on a secondary analysis, highlighting PPE initiatives with FBHPs.